FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Rendy, Rendy; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to study the effect of liquidity, leverage, and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2017. This study used a non-probability sample method with a purposive sampling technique. The number of samples used in this study were 96 samples. The results of this study indicate that liquidity (CR) has a significant and negative effect on firm value, leverage (DAR) does not affect on firm value, and profitability (NPM) has a significant and positive effect on firm value. leverage (DAR), and profitability (NPM) together against company value.